2002
DOI: 10.1124/jpet.302.1.205
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Inhibition of Thyroxine-Induced Bone Resorption in the Rat by an Orally Active Vitronectin Receptor Antagonist

Abstract: An excess of thyroid hormone results in increased bone turnover and loss of bone mass in humans. Exogenous administration of thyroid hormone to rats has served as a model of human hyperthyroidism in which antiresorptive therapies have been tested. We have further refined this model of thyroxine (T4)-induced turnover in the rat. Daily administration of T4 to aged rats for as short as 1 week resulted in elevated bone resorption determined by significantly higher urinary deoxypyridinoline (Dpd) compared with vehi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 38 publications
0
18
0
4
Order By: Relevance
“…Unrelated to cancer, angiogenesis may be pathological, e.g., in certain retinopathies, or it may be desirable in the context of ischemic tissues. Expression of a TR on ␣v␤3 of osteoclasts appears to underlie a model of thyroid hormone-induced bone mass loss in the mouse (3,67) or rat (23). The integrin is displayed to a lesser extent on other cells, e.g., muscle cells (59), and on platelets (26), and specific thyroid hormone analogs have been shown to induce human platelet aggregation in vitro (44).…”
Section: Integrin ␣V␤3 the Thyroid Hormone Plasma Membrane Receptormentioning
confidence: 99%
“…Unrelated to cancer, angiogenesis may be pathological, e.g., in certain retinopathies, or it may be desirable in the context of ischemic tissues. Expression of a TR on ␣v␤3 of osteoclasts appears to underlie a model of thyroid hormone-induced bone mass loss in the mouse (3,67) or rat (23). The integrin is displayed to a lesser extent on other cells, e.g., muscle cells (59), and on platelets (26), and specific thyroid hormone analogs have been shown to induce human platelet aggregation in vitro (44).…”
Section: Integrin ␣V␤3 the Thyroid Hormone Plasma Membrane Receptormentioning
confidence: 99%
“…While the expression of TR isoforms has been documented in both rodent (Williams et al 1994) and human (Siddiqi et al 2002) osteoblast cell lines and primary cultures of rat (Bland et al 1997) and human (Siddiqi et al 2002) osteoblasts, there is only one report from more than a decade ago, which has provided evidence for non-genomic effects of T 3 on bone (Lakatos & Stern 1991). More recently, Hoffman et al (2002) reported that the RGD peptide blocked bone demineralisation in rats induced by thyroid hormone raising the possibility that the integrin a V b 3 protein might be the initiation site for nongenomic actions of thyroid hormone on osteoblasts. The aim of our study therefore was to examine whether T 3 or T 4 were able to rapidly activate the MAPK intracellular signalling cascade and investigate whether this activation was initiated at the integrin a V b 3 cell surface receptor.…”
Section: Introductionmentioning
confidence: 99%
“…The plasma membrane thyroid hormone receptor that mediates a number of the nongenomic actions of thyroid hormone is on integrin avb3 [57]. The receptor that is involved in experimental thyroid hormone-induced bone resorption appears to be on an integrin [79]. Thus, it is conceivable that the blocking of iodothyronine-induced bone-resorbing action of T 4 by CT may involve action of the latter at the integrin.…”
Section: Thyroid Hormone and Actions Of Calcitoninmentioning
confidence: 91%
“…At the cell nucleus level of thyroid hormone action, bone is described as a nuclear thyroid hormone receptor (TR)-a 1 -responsive tissue [77], whereas bone chondrocytes are TRb-responsive [78]. However, Hoffman et al in 2002 confirmed a rapid effect of thyroid hormone in rabbits to decrease bone mass decrease and also showed that a proprietary anti-integrin agent, SB273005, prevented the increase in urinary Dpd, an index of bone resorption, in T 4 -treated rats [79]. This report antedated the description of the thyroid hormone receptor on integrin avb3 [57] and can in this context now be proposed to reflect a relatively acute resorptive effect of T 4 on bone which is nongenomic and involves the plasma membrane (integrin) receptor for the hormone.…”
Section: Actions Of Thyroid Hormone On Bone At the Molecular Level: Fmentioning
confidence: 95%
See 1 more Smart Citation